2018
DOI: 10.1088/1361-6501/aaa509
|View full text |Cite
|
Sign up to set email alerts
|

Application of process tomography in gas–solid fluidised beds in different scales and structures

Abstract: Gas-solids fluidised beds are commonly used in particle-related processes, e.g. for coal combustion and gasification in the power industry, and coating and granulation process in the pharmaceutical industry. Because the operation efficiency depends on the gas-solids flow characteristics, it is necessary to investigate the flow behaviour. This paper is about application of process tomography, including electrical capacitance tomography (ECT) and microwave tomography (MWT), in multi-scale gas-solids fluidisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Moreover, u mf can be calculated theoretically, according to Kunii et al (1991), where w s is the sphericity, ε mf is the void fraction of under the minimal fluidization state, it is expressed as TFBs with three different inclination angles are considered. The prototype of the fluidized bed is a dryer which has been introduced in the previous publication (Wang et al, 2018;Ge et al, 2016), and the particle properties (shown in Table 2 and Table 4) are determined based on the cellulose particles in previous studies (Che et al, 2018(Che et al, , 2020.…”
Section: Minimal Fluidization Velocitymentioning
confidence: 99%
“…Moreover, u mf can be calculated theoretically, according to Kunii et al (1991), where w s is the sphericity, ε mf is the void fraction of under the minimal fluidization state, it is expressed as TFBs with three different inclination angles are considered. The prototype of the fluidized bed is a dryer which has been introduced in the previous publication (Wang et al, 2018;Ge et al, 2016), and the particle properties (shown in Table 2 and Table 4) are determined based on the cellulose particles in previous studies (Che et al, 2018(Che et al, , 2020.…”
Section: Minimal Fluidization Velocitymentioning
confidence: 99%
“…The data acquisition rate is 120 frames/s for each sensor and 1000 sets of data are acquired for each case. Wang et al (2018) gives a detailed description of the ECT image reconstruction, and concludes that the Landweber iteration algorithm is suitable to reconstruct solids distribution and identify the flow regime in gas-solids fluidized beds.…”
Section: Ect Sensor Design and Image Reconstructionmentioning
confidence: 99%
“…Normally, the riser shape of a CFB can be circular, square and rectangular (Wang et al, 2018), which has been studied a lot by the researchers, especially the circular CFB. For example, Rao et al (2010) studied the effect of the column diameter and the bed height on the minimum fluidization velocity, and found that the minimum fluidization velocity insignificantly increases as the diameter of the fluidization column is reduced, or if the height of the bed is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PT (Process Tomography) (Gladden, 1997;Wang et al, 2018) Mastering this subject requires students to gain a deep understanding in a number of relevant areas, in particular, two major concepts, i.e. the forward problem and the inverse problem (Munck, Faes, & Heethaar, 2000).…”
Section: Introductionmentioning
confidence: 99%